Penguatan Kapasitas Manajerial Koperasi Desa untuk Mewujudkan Pembangunan Ekonomi Berbasis Komunitas - Ade Maya Mei Shanty; Makhrani; Silviana Batubara (Yayasan Perguruan Kampus, 2025)
Community based economic development requires the active role of local institutions, particularly village cooperatives, as key drivers of community economic activities. However, many village cooperatives face managerial challenges that hinder their organizational performance and their contribution to rural development. This study aims to analyze the strengthening of managerial capacity in village cooperatives as a strategic effort to enhance community-based economic development. Using a qualitative approach with a case study method, the research was conducted in three village cooperatives in District Tapanuli Selatan. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that cooperatives implementing managerial training, digital financial systems, and local partnerships demonstrate improvements in operational efficiency, member participation, and economic resilience. The discussion emphasizes that strong managerial capacity plays a crucial role in building adaptive, participatory, and locally competitive cooperatives. The study recommends sustained policy support in the form of training programs, digital transformation incentives, and integrated assistance for village cooperatives across Indonesia.